FAKTOR-FAKTOR YANG MEMENGARUHI VOLUNTARY AUDITOR SWITCHING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mahindrayogi, Komang Trisdia; Suputra, I Dewa Gde Dharma (E-Jurnal Akuntansi, 2016)
Auditor switching is the alternation of the public accounting firm that performed by a company,the alternation is possible because of the obligation (mandatory) and also voluntary (voluntary). This study purposes to determine the influence of public ownership, the growth of the company, going concern opinion, and the financial difficulties of the voluntary auditors switching. This study used logistic regression analysis with a sample of 42 companies based on the results of purposive sampling with criteria established. The test results showed that the variables of public ownership and growth of companies that proxied by the ratio of sales growth give a positive effect on voluntary auditor switching.The going concern opinion and financial difficulties do not affect the voluntary switching auditors.
Keywords: Voluntary Auditor Switching, Public Ownership, Growth Company, Going Concern Opinion, Financial Difficulties